Research Progress on Initiation and Development Mechanism of Embankment Piping - LIAO Zhihao; CHEN Hao; ZHU Shaokun; LI Mao (Renmin Zhujiang)
Piping is one of the main causes of embankment failure,and studying the initiation and development mechanism of piping has profound significance for the reinforcement and the prevention of water disasters in embankment engineering.By reviewing the relevant research on embankment piping in China and abroad,the initiation conditions of piping are summarized from both geometric and hydraulic aspects.The influence of factors such as soil particle size distribution,soil layer structure, compactness,seepage diameter,anti-seepage wall,water head change,water flow pattern,and seepage direction on embankment piping is discussed.The capillary model,seepage-pipe flow coupling model,seepage generalized model,three-phase coupling model,transient piping model,local erosion model,and solid-liquid coupling model that describe the occurrence and development process of piping are summarized.Based on current research,the limitations of mathematical models of piping are discussed,and the shortcomings of research on the influencing factors of piping are revealed.Moreover,prospects for future research work on the initiation and development mechanism of piping are proposed.